Shelf-Life Assessment Of Carrier Based Formulations Of Trichoderma Mutants (Journal of Plant Disease Sciences, 2022)
In present study six different substrates (talcum powder, lignite, charcoal, sawdust, compost and fly ash) were used to test the shelf life of the most virulent isolates of Trichoderma harzianum (AkTr 2GM5) and Trichoderma hamatum (AkTm1GM5) mutant’s upto 180 days. Maximum cfu/g 154.50 x 106 and 45.50 x 106 were obtained at 30 and 180 days after storage in the Trichoderma harzianum talc-based formulation respectively, and the lowest (16.25 x 106) in fly ash formulation. Furthermore, Trichoderma hamatum talc based formulations exhibit maximum cfu/g values of 156.75 x 106 and 41.50 x 106 at 30 and 180 days after storage, respectively.
Keywords: Formulations; Mutant; Shelf life; Trichoderma